2011
DOI: 10.1159/000327968
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Three Aquaglyceroporins from <i>Trypanosoma brucei</i> in Osmoregulation and Glycerol Transport

Abstract: Previous studies using bloodstream form Trypanosoma brucei have shown that glycerol transport in this parasite occurs via specific membrane proteins, namely a glycerol transporter and glycerol channels [1]. Later, we cloned, expressed and characterized the transport properties of all three aquaglyceroporins (AQP1-3) [2], which were found permeable for water, glycerol and other small uncharged solutes like dihydroxyacetone [3]. Here, we report on the cellular localization of TbAQP1 and TbAQP3 in bloodstream for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 31 publications
1
51
2
Order By: Relevance
“…3A, Upper), whereas GFP AQP3 localized to this region and also to the plasma membrane (Fig. 3A, Lower), as demonstrated previously for native AQP3 (26). These results were confirmed by confocal microscopy and were indistinguishable in an aqp2/aqp3 or aqp2 background.…”
Section: Aqp2 Is Restricted To the Flagellar Pocket Specifically In Bsupporting
confidence: 87%
See 2 more Smart Citations
“…3A, Upper), whereas GFP AQP3 localized to this region and also to the plasma membrane (Fig. 3A, Lower), as demonstrated previously for native AQP3 (26). These results were confirmed by confocal microscopy and were indistinguishable in an aqp2/aqp3 or aqp2 background.…”
Section: Aqp2 Is Restricted To the Flagellar Pocket Specifically In Bsupporting
confidence: 87%
“…AQP3 is dispersed over the plasma membrane, whereas AQP1 is predominantly restricted to the flagellum (26). We have now shown that AQP2 displays a distinct localization that is specific to bloodstream-stage cells, being retained in the flagellar pocket.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…There are notable similarities at both the morphological and biochemical level between T. brucei brucei swelling caused by TLF-1 and swelling caused by hypotonic stress. The observed cytoplasmic volume increase observed in TLF-1-treated T. brucei brucei resembles cell swelling caused by hypotonic shock, although RVD after hypotonic shock facilitates recovery of cell volume after a short time (9,58). Both TLF-1 treatment and hypotonic shock are associated with potassium ion efflux and calcium ion influx in T. brucei brucei (9,59,60).…”
Section: Discussionmentioning
confidence: 92%
“…One of the first such proteins identified was a receptor type adenylate cyclase (6) that is likely involved in sensing the extracellular environment and relaying signals via synthesis of cAMP, and recent work on this family of proteins has uncovered roles for evasion of host innate immunity (7) and in social motility in insect stage procyclic forms (PFs) (8 -10). Furthermore, a variety of putative transporters and channels are present in the flagellar membrane (5), where they may play roles in nutrient or ion uptake and potentially in nutrient or solute sensing (11). Other important roles for the flagellar membrane are attachment to the salivary gland epithelium in the tsetse fly (12), flagellar adherence of gametes during mating (13), and attachment of the tip of the new flagellum to the body of the old flagellum during parasite replication, where attachment of flagella is required for cleavage furrow formation and proper cell division (14 -16).…”
mentioning
confidence: 99%